Mucosal integrin α4β7 blockade fails to reduce the seeding and size of viral reservoirs in SIV‐infected rhesus macaques. Issue 2 (23rd January 2021) - Ziani, Widade; Shao, Jiasheng; Fang, Angela; Connolly, Patrick J.; Wang, Xiaolei; Veazey, Ronald S.; Xu, Huanbin
Abstract: Cellular viral reservoirs are rapidly established in tissues upon HIV‐1/SIV infection, which persist throughout viral infection, even under long‐term antiretroviral therapy (ART). Specific integrins are involved in the homing of cells to gut‐associated lymphoid tissues (GALT) and inflamed tissues, which may promote the seeding and dissemination of HIV‐1/SIV to these tissue sites. In this study, we investigated the efficacy of prophylactic integrin blockade (α4β7 antibody or α4β7/α4β1 dual antagonist TR‐14035) on viral infection, as well as dissemination and seeding of viral reservoirs in systemic and lymphoid compartments post‐SIV inoculation. The results showed that blockade of α4β7/α4β1 did not decrease viral infection, replication, or reduce viral reservoir size in tissues of rhesus macaques after SIV infection, as indicated by equivalent levels of plasma viremia and cell‐associated SIV RNA/DNA to controls. Surprisingly, TR‐14035 administration in acute SIV infection resulted in consistently higher viremia and more rapid disease progression. These findings suggest that integrin blockade alone fails to effectively control viral infection, replication, dissemination, and reservoir establishment in HIV‐1/SIV infection. The use of integrin blockade for prevention or/and therapeutic strategies requires further investigation.